2013
DOI: 10.1111/vox.12088
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New German blood donor questionnaire

Abstract: The new DHQ was acceptable to the vast majority of donors. Potential donors who were older, male gender and less educated were most at risk of refusing to donate and may benefit from educational interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 8 publications
2
14
0
Order By: Relevance
“…Still, demographic changes in Germany will most likely lead to fewer younger donors in the future on the one hand and to an increasing need of blood and blood products due to an ageing population on the other [17,18]. Therefore, the reasons for deferral need to be clearly communicated to potential donors, and low-risk donors should be recruited continuously in order to provide enough appropriate blood products for patients in need.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, demographic changes in Germany will most likely lead to fewer younger donors in the future on the one hand and to an increasing need of blood and blood products due to an ageing population on the other [17,18]. Therefore, the reasons for deferral need to be clearly communicated to potential donors, and low-risk donors should be recruited continuously in order to provide enough appropriate blood products for patients in need.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the UDQ was acceptable to the majority of donors [17] and demonstrated its superiority compared to the established DQ regarding comprehensibility as well as donor adherence [3]. Furthermore, results of a cognitive interview evaluation of the new AABB DQ found no evidence that blood donors modified their answers due to a perceived inappropriate sensitive character of questions [10].…”
Section: Discussionmentioning
confidence: 99%
“…In Germany, a uniform DHQ was introduced (for voluntary use), which addressed sexual behavior directly to avoid donors' self-assessment of their infection risk. Pre-evaluation studies showed a higher percentage of correct answers about sexual risk behavior [19] compared to the established DHQs, but a notable portion of donors considered those questions as too personal [20,21]. However, it was also shown that questions dealing with sexual risk behaviors were accepted -despite the discomfort -if the questions were demonstrated to potentially increase blood safety [20].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-evaluation studies showed a higher percentage of correct answers about sexual risk behavior [19] compared to the established DHQs, but a notable portion of donors considered those questions as too personal [20,21]. However, it was also shown that questions dealing with sexual risk behaviors were accepted -despite the discomfort -if the questions were demonstrated to potentially increase blood safety [20]. Therefore, in addition to appropriate donor education, the proposed uniform DHQ can help reduce the proportion of donors with sexually transmitted TTI.…”
Section: Discussionmentioning
confidence: 99%
“…In a second study roughly 4,000 donors were included in a cross-sectional study of two blood establishments which also participated in the initial evaluation of the NDQ [42]. They were asked to complete an anonymous paper-based questionnaire containing questions about donor comfort with intimate questions dealing with sexual activities and the possible impact on participants' willingness to participate in future.…”
Section: Additional Donor Questionnaire Studiesmentioning
confidence: 99%